Uterine artery embolization in the treatment of uterine fibroids and the preservation of reproductive health in women 40 years of age and older: A retrospective study - Alina V. Solovyeva; Larisa A. Chegus; Ekaterina Yu. Aleynikova; Sergey I. Semenchenko; Oksana I. Menshikh; Anzhelika E. Kasparova (IP Berlin A.V., 2024)
Aim. To evaluate the effect of uterine artery embolization (UAE) on reproductive health in women 40 years and older. Materials and methods. A retrospective study was conducted at the perinatal center of the District Clinical Hospital of Khanty-Mansiysk. Patients were divided into two groups: the main group (group 1; n=57) included women with uterine fibroids after UAE, and the control group (group 2; n=42) included women without a history of uterine fibroids. Results. Women with uterine fibroids were statistically more likely to have grade 1 obesity (χ2=4.39; p=0.04) and less likely to have normal body weight (χ2=8.73; p=0.00) compared to women without fibroids. Smoking increased the risk of uterine fibroids twofold (χ2=4.49; p=0.03; odds ratio 1.97; confidence interval 0.64-6.11). More women with uterine fibroids had a history of abortions (n=42; 73.7%) than those without uterine fibroids (n=19; 45.2%; χ2=8.27; p=0.01). The most common gynecological comorbidities in women with uterine fibroids included inflammatory disease of the uterus (N71), endometrial polyp (N84), and endometriosis (N80); p0.05. The most common extragenital diseases in patients with uterine fibroids included thyroid disease, hypertension, and iron deficiency anemia (p0.05). Contour SE embolization agent with spherical particles was more often associated with pain (χ2=0.18; p=0.67) and less often with fever (χ2=4.47; p=0.03). There was a decrease in the number of short menstrual cycles (less than 24 days) from the moment before surgical treatment and after 24 months (χ2=34.580; p0.001) and an increase in the number of cycles of 24-38 days (χ2=14.887; p=0.005). At 24 months after UAE, there were more women with a menstrual period of less than 3 days (χ2=10.385; p=0.035) and fewer with a menstrual period of more than 8 days (χ2=34.573; p0.001). Ultrasound showed a decreased ovarian reserve at 6, 12 and 24 months after UAE (p0.05). Conclusion. When assessing the reproductive health of women 40 years and older after embolization of the uterine arteries, it was found that this method of treatment of symptomatic uterine fibroids leads to a decrease in the duration and heaviness of menstruation but increases the risk of an ovarian reserve decrease.